THE INFLUENCE OF THE VILLAGE FINANCIAL SYSTEM, COMPETENCE OF VILLAGE APPARATUS, AND COMMUNITY PARTICIPATION ON ACCOUNTABILITY IN VILLAGE FUND MANAGEMENT - Damayanti, Ni Luh Gede Adelia; Sujana, I Ketut (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This research aims to examine the influence of the implementation of the village financial system, the competence of village officials, and community participation on the accountability of village fund management. The total or census technique was used to choose 72 respondents for the study sample. Using a questionnaire distribution approach, the study was carried out. A method known multiple linear regression analysis was employed for the data analysis. The investigation findings point out that there is a positive relationship between accountability in managing village funds, the competence of village officials, and community participation. Specifically, accountable management of village funds is enhanced by implementing the village financial system.